Related factors of actual turnover among nurses: a cross-sectional study - Rindu Rindu; Muhammad Hafizurrachman (Intelektual Pustaka Media Utama, 2023)
Turnover exacerbates the global nursing shortage; the loss of skilled and expert nurses has a negative impact on patient outcomes. The study examined the influence of job satisfaction, work environment, leadership styles, organizational commitment and work-family support on actual turnover among nurses working in the hospital of Indonesia. A cross-sectional survey was carried out in Jakarta, Indonesia. The sample in this study was nurses who leave the jobs from hospital during period of time October 2019 to October 2020. A total of 170 nurses responded to the survey. Nurses reported poor leadership style (2.84±0.82), organization commitment (2.99±0.76), as well as dissatisfaction with organization (2.76±0.80) and leadership support (2.89±0.89). Job satisfaction (p=0.007), work environment (p=0.032), leadership style (p=0.001), organizational commitment (p=0.010), and work-family support (p=0.026) remained statistically significant affected turnover. The findings of this study emphasize the critical role of satisfaction, organizational commitment, work-family support, and leadership style in determining nurse intention to stay and provide employers with a road map for reducing turnover. Future studies may need to understand more deeper regarding the actual turnover experience and its associated factors using longitudinal or qualitative studies.